Enhancing Economic Development and Job Creation in Addis Ababa : The Role of the City Administration - World Bank Group (World Bank, Washington, DC, 2018)
Addis Ababa will play a major role in Ethiopia’s aspirations to reach middle income status, yet institutional inefficiencies currently hamper structural transformation. Addis Ababa contributes a third of Ethiopia’s manufacturing sector GDP and over half of urban employment. Yet, current policy restrictions on access to land already seem to be leading to a declining share of employment in the manufacturing sectors in which Addis Ababa is specialized, without a significant increase in the high value added sectors policy makers seek for the city. Policy makers at the city as well as national level therefore need to rapidly undertake efforts towards instituting a conducive environment for the development and attraction of these higher tech sectors. Given that unemployment in Addis Ababa is already the highest in urban Ethiopia, urgent action is needed to encourage economic succession to provide sources of employment for citizens. This report provides recommendations on the role of the City Administration in economic development and recommends a focus on better access to land, simpler procedures for domestic and diaspora investors, more competitively targeted enterprise support and increased capacity of the city administration.